Divergent coronary flow responses to uridine adenosine tetraphosphate in atherosclerotic ApoE knockout mice - Teng, Bunyen (Purinergic Signal, 2017)
Uridine adenosine tetraphosphate (Up(4)A) exerts potent relaxation in porcine coronary arteries that is reduced following myocardial infarction, suggesting a crucial role for Up(4)A in the regulation of coronary flow (CF) in cardiovascular disorders. We evaluated the vasoactive effects of Up(4)A on CF in atherosclerosis using ApoE knockout (KO) mice ex vivo and in vivo. Functional studies were conducted in isolated mouse hearts using the Langendorff technique. Immunofluorescence was performed to assess purinergic P2X(1) receptor (P2X(1)R) expression in isolated mouse coronary arteries. In vivo effects of Up(4)A on coronary blood flow (CBF) were assessed using ultrasound. Infusion of Up(4)A (10(−9)–10(−5) M) into isolated mouse hearts resulted in a concentration-dependent reduction in CF in WT and ApoE KO mice to a similar extent; this effect was exacerbated in ApoE KO mice fed a high-fat diet (HFD). The P2X(1)R antagonist MRS2159 restored Up(4)A-mediated decreases in CF more so in ApoE KO + HFD than ApoE KO mice. The smooth muscle to endothelial cell ratio of coronary P2X(1)R expression was greater in ApoE KO + HFD than ApoE KO or WT mice, suggesting a net vasoconstrictor potential of P2X(1)R in ApoE KO + HFD mice. In contrast, Up(4)A (1.6 mg/kg) increased CBF to a similar extent among the three groups. In conclusion, Up(4)A decreases CF more in ApoE KO + HFD mice, likely through a net upregulation of vasoconstrictor P2X(1)R. In contrast, Up(4)A increases CBF in vivo regardless of the atherosclerotic model.